ANALISIS MODEL PEMBELAJARAN DARING DAN BLENDED LEARNING TERHADAP HASIL BELAJAR SISWA - Nizar Haris Hamzah (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
The purpose of this study was to determine the relationship between online learning and blended learning on physical education learning outcomes during the COVID-19 pandemic. This study uses a descriptive quantitative survey. The sample of this research is 132 students in cluster 3 sub-districts of Cirebon district. The data obtained in this study were Likert scale questionnaires and daily test documents of student learning outcomes in one semester. The analysis technique used is multiple relationship analysis. Based on the data analysis, it can be concluded that the implementation of the online learning model and the Blended Learning learning model has no relationship to the student learning outcomes obtained. p-value (sig) 0.000 <0.05 (5%), person correlation coefficient 0.143